Analysis of global visual practices in the development of game projects - Kohutiak, Oleksandr; Babii, Nadiia (Art and Design, 2026)
The relevance of the study is conditioned by the growing influence of visual practices on the development of aesthetics, narrative and user experience in video games, which makes them one of the key factors in the development of the global gaming industry. The purpose of the study was to analyse the leading visualisation trends that determine the artistic and technological features of game worlds of the last decade. The study was based on a comparative, and system and analytical approach, and included content analysis of games, interpretation of their visual design, and review of scientific sources. In total, 23 game projects of various genres and styles were analysed, which allowed identifying patterns in the development of the visual component of the industry and tracing the relationship between aesthetic solutions, technological innovations and commercial success. The sample included both high-budget AAA projects and independent indie games, which provided a more comprehensive vision of contemporary approaches to design. The analysis showed that current practices cover stylised graphics, cel-shading, pixel art, sumi-e and the latest solutions based on artificial intelligence, including procedural art and generative stylisation. It was revealed that an important role is played by the design of the user interface and user experience, which determines the intuitiveness and convenience of interaction, and "environmental storytelling" as a form of wordless narrative that deepens the emotional connection of the user with the game world. Special attention was paid to the use of cinematic techniques and interactive directing, which provide a hybrid gaming experience and bring video games closer to other forms of audiovisual art. The results of the study can be used by game designers, artists, educators, and digital media researchers as an analytical base for developing visually holistic and commercially successful games, and in the field of educational design, cultural analytics, and creating an inclusive visual environment